Media release - Perron, Marshall, 1942-
tag=1 data=MEDIA RELEASE tag=2 data=PERRON, MARSHALL tag=8 data=EMPLOYMENTORIGINES tag=9 data=TIWI DESIGNSTHURST ISLAND%TRAINING INITIATIVES tag=24 data=CHIEF MINISTER tag=27 data=T-0869-90 tag=61 data=14 tag=62 data=SEP tag=63 data=1990